KARAKTERISTIK ANAK BERKEBUTUHAN KHUSUS - Eki Zakiyah; Yahdinil Firda Nadhira (STKIP Subang, 2024)
Autism is a behavioral disorder in which sufferers are only interested in their own mental activities such as daydreaming or fantasizing. Behavioral disorders can change lack of social interaction, Avoidance of eye contact, difficulty in developing language, and repetitive behavior. Autistic children are children who experience severe developmental disorders which, among other things, affect the way they communicate. interact and live life Autism is a complex developmental disorder that involves problems with communication, social interaction and imaginative activity. The term autism is still unknown to many people.what is meant by autism so that often the problem of autism is considered as something negative This article aims to provide a general picture of the characteristics, causes, and intervention strategies for individuals with autism, and highlight the importance of social inclusion and family support in improving their quality of life.